Marcas corporais na toxicomania - Pereira, Joana Caldas Pinheiro Malta (2011)
It is a psychoanalytic study on drug abuse and bodily marks whose goal was to understand the relation addicts establish with their bodies, considering the enjoyment by the ingestion of drugs and the joy in marking their skin. Nowadays, the usage of the body has become a common practice by highlighting of sensuality and among drug addicts is common to have tattoos on the body, and some of them on large area of it. Firstly, we presented the studies about the subject physical disposition and his position in relation to drug abuse, secondly the relation among body, libido, identity and drug addiction and, finally, we presented the results of field research developed at the Institute RAID. We analyzed the stories about the body markings of three drug addicts and we realized that manipulating the body, stimulating in it internal feelings by the use of drugs and external marking it is a way of putting together an identity, appropriating the body and make it alive